PREVALENCE OF DEPRESSION AND SUICIDAL IDEATION AMONG PATIENTS IN THE MAIN COVID-19 HOSPITALS IN PENINSULAR MALAYSIA - bin Kassim, Mohd Shaiful Azlan; Ahmad, Noor Ani; Silim, Umi Adzlin; Abdullah, Muhammad Najib; Harun, Norazam; Dollah, Siti Nordiana; Sahril, Norhafizah; Rezali, Muhammad Solihin; Chan Ying Ying; Redzuan, Noor Izuana; et al. (Malaysian Journal of Public Health Medicine, 2023)
The outbreak of pandemic disease is catastrophic and caused negative psychological effects among patients, healthcare workers and their surroundings. This study aims to determine the prevalence of depression and suicidal ideation among stable hospitalized COVID-19 patients. This is a cross-sectional study with web-based online survey involving 401 stable hospitalized COVID-19 patients aged 18 years above who were selected via quota sampling technique. The questionnaire consists of socio-demographic profile, Patient Health Questionnaire 9 items (PHQ-9) and Brief COPE (Coping Orientation to Problems Experienced). The identified probable cases of depression and suicidal ideation were subsequently referred to psychiatrists. The prevalence of depression and suicidal ideation were 7.5% and 4.0% respectively. The prediction model revealed that females [aOR=5.29 (95% CI: 1.34, 20.80)], age 35-49 years old [aOR=7.47 (95% CI: 1.78, 31.30)], adopting behavioral disengagement [aOR=1.94 (95% CI: 1.31, 2.87)] and self-blame [(aOR = 1.74, 95% CI: 1.31, 2.30)] as coping strategies, were significant predictors of depression. The findings estimate mental health burden among COVID-19 patients in Malaysia. The establishment of continuous mental health surveillance is essential in managing cases of depression and suicidal ideation.